2023
DOI: 10.1021/acsabm.3c00226
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Inspired Peptide Antifouling Biocide: Coating Compatibility, Field Validation, and Environmental Stability

Patrick Cahill,
Thomas M. Grant,
David Rennison
et al.

Abstract: This study reports the development of a class of eco-friendly antifouling biocides based on a cyclic dipeptide scaffold, 2,5-diketopiperazine (2,5-DKP). The lead compound cyclo(N-Bip-l-Arg-N-Bip-l-Arg) (1) was synthesized in gram amounts and used to assess the compatibility with an ablation/hydration coating, efficacy against biofouling, and biodegradation. Leaching of 1 from the coating into seawater was assessed via a rotating drum method, revealing relatively stable and predictable leaching rates under dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Nonoptimized release profiles (or even a lack of release data) combined with limited insights into paint composition and compound distribution often make it challenging to explain why a promising lead from the laboratory fails to function in the field. Several of our lead compounds have been studied in the field, with greatly ranging results. , Both synthetic analogs of phidianidine and a lead 2,5-DKP were shown to display detectable reductions in biofouling development. The phidianidine analog efficiently prevented microfouling for up to 84 days (duration of the study) but with no effect against macrofoulers (Figure ).…”
Section: Coating and Field Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonoptimized release profiles (or even a lack of release data) combined with limited insights into paint composition and compound distribution often make it challenging to explain why a promising lead from the laboratory fails to function in the field. Several of our lead compounds have been studied in the field, with greatly ranging results. , Both synthetic analogs of phidianidine and a lead 2,5-DKP were shown to display detectable reductions in biofouling development. The phidianidine analog efficiently prevented microfouling for up to 84 days (duration of the study) but with no effect against macrofoulers (Figure ).…”
Section: Coating and Field Studiesmentioning
confidence: 99%
“…After this time, biofouling overwhelmed the performance of the coating, consistent with leaching kinetics that suggest a rapid depletion of the active antifouling ingredient (Figure ). It is not unlikely that the performance of both could be significantly improved with optimized paint/coating formulations.…”
Section: Coating and Field Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pérez et al reported the isolation and AF activity evaluation of five natural alkaloids from trees of the Atlantic rainforest, namely olivacine (60), uleine (61), and N-methyltetrahydroellipticine (62) from Aspidosperma austral, and the furoquinoline alkaloids kokusaginine (63) and flindersiamine (64) (Figure 2) from Balfourodendron riedelianum [54]. Alkaloids 62 and 63 displayed the most active anti-settlement activity against mussel M. edulis platensis [54].…”
Section: Rosin-based Coatingsmentioning
confidence: 99%